IMPLEMENTASI ETIKA SYARIAH MARKETER PADA PT. BANK BRISYARIAH KANTOR CABANG PEMBANTU KEPANJEN - Fariz, Mohammad Jazmi; Rahayu, Yayuk Sri (Fakultas Ekonomi, UIN Maliki Malang, 2018)
ABSTRACTShariah marketing is a strategic business discipline that directs the process of creating, offering and changing the value of an initiator to its stakeholders, which in its entirety conforms to the covenants and principles of muamalah (business) in Islam. This study aims to find out how the implementation of sharia ethics marketer at bank BRISyariah KCP Kepanjen.This research uses a qualitative descriptive approach where the goal is to describe systematically about the focus of research. The limitations in this study examine the principles of sharia ethics of marketer. Â Subjects in this study there are five informants. Data were collected by direct observation, interview, and documentation. The data analysis used are data reduction, data presentation and conclusion drawing with triangulation method as a validity test.The result of this research shows that Bank BRISyariah KCP Kepanjen has implemented 9 sharia ethics of marketers consist of have a spiritual personality, behave kindly and sympathetically (shiddiq), be fair in business (al-'adl), serving and humble (khidmah), keeping promises and not cheating, honest and trustworthy (al-amanah), do not like to suspect (su'uzh-zhan), do not like to vilify (ghibah), and do not do bribes (riswah).